Paper Families : Identity, Immigration Administration, and Chinese Exclusion - Lau, Estelle T. (Book collections on Project MUSE., 2006)
A look at how the Chinese Exclusion Act and later legislation affected Chinese American communities, who created fictitious ""paper families"" to subvert immigration policies.